2022
DOI: 10.12669/pjms.38.5.5798
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of neutrophil-to-lymphocyte, lymphocyte-to-monocyte and platelet-to-lymphocyte ratio among patients with COVID-19 pneumonia: A retrospective study

Abstract: Objectives: Our study was aimed to investigate the clinical characteristics of the patients with COVID-19 pneumonia and research new diagnostic methods for the disease. Methods: In this retrospective study, medical records of 46 novel coronavirus-infected pneumonia (NCIP) patients and 30 healthy individuals in the two multiple hospitals from January 2020 to March 2020 were studied. Clinical characteristics, chest computed tomographic (CT) scans, medicine treatment and laboratory information were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
2
1
1
Order By: Relevance
“…17 Another study conducted in China has shown that NLR is associated with increased severity of the disease and also the mortality in patients with COVID-19 infection. 18 In the current study, no correlation was found between severity of disease and hemoglobin level and platelet count. A study conducted by Taj et al also described no relation between these parameters and clinical severity groups 3 but another study conducted by Rehman T et al showed significant difference with respect to hemoglobin and platelet count.…”
Section: Discussioncontrasting
confidence: 65%
“…17 Another study conducted in China has shown that NLR is associated with increased severity of the disease and also the mortality in patients with COVID-19 infection. 18 In the current study, no correlation was found between severity of disease and hemoglobin level and platelet count. A study conducted by Taj et al also described no relation between these parameters and clinical severity groups 3 but another study conducted by Rehman T et al showed significant difference with respect to hemoglobin and platelet count.…”
Section: Discussioncontrasting
confidence: 65%
“…The platelet-lymphocyte ratio (PLR) is a novel inflammatory marker and recent studies show that a high PLR reflects inflammation. 16 Neutrophil-lymphocyte ratio (NLR) is used as a marker of inflammation. A higher ratio, indicative of a hyperinflammatory situation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, thrombocytes play an important role in the regulation of a number of inflammatory processes [13,14]. Changes in white blood cells, lymphocyte, and platelet counts are strongly associated with COVID-19 pneumonia [15]. However, these biological parameters are still nonspecific, and the addition of a combination marker, such as the platelet-to-lymphocyte ratio (PLR), may provide an additional justification for better distinguishing between individuals at risk of having a severe SARS--CoV-2 infection and those who are not.…”
Section: Introductionmentioning
confidence: 99%